Organic compounds in natural waters : analysis and determination - Crompton, T. R. (CRC Press/Balkema, an imprint of the Taylor & Francis Group, 2014)
"The potential health hazards that might arise from the presence of Organic Substances in Water are a matter of increasing concern to the water industry, environmentalists and the general public alike. This comprehensive reference draws together and systematises the vast body of information available on the occurrence and determination of organic substances in natural waters. Determination of Organic Substances in Natural Waters provides a comprehensive description of organic substances in waters. Methods are provided in broad outline, with guidance on their applicability, their comparative advantages and disadvantages, possible interferences, sensitivity and detection levels. The book is an essential reference for analytical chemists working in industry, water utilities, government & non government organisations and regulatory agencies and environmental & analytical consultants"-- Provided by publisher.
Keywords: Organic compounds -- Environmental aspects.; Water -- Pollution.; Organic compounds -- Analysis.; Saline waters -- Analysis.; Fresh water -- Analysis.; Water -- Pollution -- Measurement.; Water chemistry.; elektronické knihy; electronic books